The Three-Dimensional Culture System with Matrigel and Neurotrophic Factors Preserves the Structure and Function of Spiral Ganglion Neuron In Vitro - Gaoying Sun; Wenwen Liu; Zhaomin Fan; Daogong Zhang; Yuechen Han; Lei Xu; Jieyu Qi; Shasha Zhang; Bradley T. Gao; Xiaohui Bai; Jianfeng Li; Renjie Chai; et al. (Neural Plasticity)
Whole organ culture of the spiral ganglion region is a resourceful model system facilitating manipulation and analysis of live sprial ganglion neurons (SGNs). Three-dimensional (3D) cultures have been demonstrated to have many biomedical applications, but the effect of 3D culture in maintaining the SGNs structure and function in explant culture remains uninvestigated. In this study, we used the matrigel to encapsulate the spiral ganglion region isolated from neonatal mice. First, we optimized the matrigel concentration for the 3D culture system and found the 3D culture system protected the SGNs against apoptosis, preserved the structure of spiral ganglion region, and promoted the sprouting and outgrowth of SGNs neurites. Next, we found the 3D culture system promoted growth cone growth as evidenced by a higher average number and a longer average length of filopodia and a larger growth cone area. 3D culture system also significantly elevated the synapse density of SGNs. Last, we found that the 3D culture system combined with neurotrophic factors had accumulated effects in promoting the neurites outgrowth compared with 3D culture or NFs treatment only groups. Together, we conclude that the 3D culture system preserves the structure and function of SGN in explant culture.